Pancytopenia: a rare cause for a common presentation. (October 2020) - Mahto, Subodh Kumar; Singh, Akanksha; Aneja, Ankita; Pasricha, Nitasha; Kumar, Brijesh
Filariasis is a major public health hazard in tropical and subtropical countries and is endemic among the Indian population. Asymptomatic microfilariaemia, elephantiasis, acute adenolymphangitis, hydrocoele and chronic lymphatic disease are its common manifestations. We hereby report a case of microfilaria found in the bone marrow presenting as pancytopenia. There was no classical feature of elephantiasis or lymphoedema present.